2010
DOI: 10.1136/thx.2010.151068.49
|View full text |Cite
|
Sign up to set email alerts
|

P248 Measuring physical recovery in the critical care population: development of the Chelsea critical care physical assessment tool (CPAx)

Abstract: Introduction The secondary physical effects of critical illness, for example, muscle atrophy, can be detrimental to functional outcome and quality of life in critical care survivors. To minimise these problems early physiotherapy in the Intensive Care Unit (ICU) is advocated. However, research to identify the optimal rehabilitation strategy is hindered by lack of an ICU specific objective measure of physical recovery. Current measures are either impairment specific, thus not capturing the full picture, or thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…After reviewing the PF tools used in adult patients in the ICU, we decided to adapt the CPAx tool. This tool was validated for adult use in 2013 (9) and consists of ten components of physical and respiratory function graded on a 6-point scale from complete dependence to independence (grades 0-5, respectively) with a maximum possible score of 50. Higher scores indicate better PF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the PF tools used in adult patients in the ICU, we decided to adapt the CPAx tool. This tool was validated for adult use in 2013 (9) and consists of ten components of physical and respiratory function graded on a 6-point scale from complete dependence to independence (grades 0-5, respectively) with a maximum possible score of 50. Higher scores indicate better PF.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we wondered whether measures of PF used in contemporary practice lacked sensitivity to detect and monitor changes in critically ill children. Three tools that have been used to measure PF in adult patients during critical illness, include the Chelsea Critical Care Physical Assessment (CPAx) tool, the ICU Mobility Scale, and the Perme ICU Mobility score (8)(9)(10). In pediatric critical care, a 2016 scoping review of literature up to 2015 reported that the Pediatric Cerebral Performance Category (PCPC), Pediatric Overall Performance Category (POPC), and Functional Status Scale (FSS) were suitable to measure functional status in large-scale studies of critically unwell children, although these outcome measures had low sensitivity for detecting small changes in motor function (7,11).…”
mentioning
confidence: 99%